Tinjauan Yuridis Tanggung Jawab Hukum Influencer atas Promosi Produk yang Menyesatkan Konsumen - Bimo Anggiarso; Aturkian Laia (INDO PUBLISHING, 2026)
The rapid growth of digital marketing has given rise to the profession of influencers, who promote products and services through social media platforms. Legal issues arise when promotional content contains false or misleading information that causes consumer losses. This study aims to analyze the legal status of influencers, their legal liability, and the effectiveness of the existing legal framework in protecting consumers. The research employs a normative legal method using statutory and conceptual approaches based on the Consumer Protection Law, the Electronic Information and Transactions Law, the Trade Law, Government Regulation Number 71 of 2019, Minister of Trade Regulation Number 31 of 2023, and the Indonesian Advertising Code of Ethics. The findings indicate that influencers may incur civil, criminal, and administrative liability for misleading promotions. However, regulatory effectiveness remains limited due to the absence of a clear legal definition, weak supervision, and the non-binding nature of advertising ethics. Strengthening regulations and supervisory mechanisms is therefore essential to enhance consumer protection.